2000
DOI: 10.1046/j.1365-2389.2000.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Root‐ and microbial‐derived mucilages affect soil structure and water transport

Abstract: The production of exudates by plant roots and microbes in the rhizosphere, together with intense wetting and drying cycles due to evapotranspiration, stimulate changes in soil structure. We have attempted to separate these two processes using an experimental model with bacterial exopolysaccharides (dextran and xanthan) and root mucilage analogues (polygalacturonic acid, PGA), and up to 10 cycles of wetting and drying. To characterize the soil structure, tensile strength, water sorptivity and ethanol sorptivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
240
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(254 citation statements)
references
References 27 publications
10
240
2
2
Order By: Relevance
“…Other authors have found strong links between microbial activity and water relations, either through pore blockage mechanisms under high substrate loads (Baveye et al 1998), or though increasing water repellency as shown in our previous work (Czarnes et al 2000). Plant root mucilages have also been well documented to increase aggregate stability (Watt et al 1993).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Other authors have found strong links between microbial activity and water relations, either through pore blockage mechanisms under high substrate loads (Baveye et al 1998), or though increasing water repellency as shown in our previous work (Czarnes et al 2000). Plant root mucilages have also been well documented to increase aggregate stability (Watt et al 1993).…”
Section: Discussionsupporting
confidence: 57%
“…Plant root mucilages have also been well documented to increase aggregate stability (Watt et al 1993). In a previous paper we (Czarnes et al 2000) reported increases in soil water repellency after amendment of soil with synthetic root mucilage. The presence of the plant in our experimental system could also have caused increased microbial activity, through the increased quantities of carbon input.…”
Section: Discussionmentioning
confidence: 85%
“…There are important factors of root/soil interaction that were not directly observable in these data, including mucilage exudation (Czarnes et al, 2000;McCully, 1999), and root hair traits (Moreno-Espíndola et al, 2007). Applying the techniques developed in this paper to investigate genotypes that contrast in mucilage exudation (Vollsnes et al, 2010) and root hair traits (Gahoonia et al, 2001) will offer compelling opportunities to probe the fundamentals of rhizosphere development.…”
Section: Discussionmentioning
confidence: 99%
“…The area of soil around plant roots, generally referred to as the rhizosphere, has also been shown to have greater levels of water repellency than bulk soil (Hallett et al 2003). Specific compounds produced by plant roots have been shown to induce water repellency (Czarnes et al 2000), but the effects could also be due to secondary microbial metabolites from root exudate decomposition. Links between hydrophobic compounds in soil and the development of water repellency have not been convincing.…”
Section: Review Soil and Water Res 3 2008 (Special Issue 1): S21-s29mentioning
confidence: 99%